2002
DOI: 10.1074/jbc.m208108200
|View full text |Cite
|
Sign up to set email alerts
|

Cation Chloride Cotransporters Interact with the Stress-related Kinases Ste20-related Proline-Alanine-rich Kinase (SPAK) and Oxidative Stress Response 1 (OSR1)

Abstract: Cells respond to stress stimuli by mounting specific responses. During osmotic and oxidative stress, cation chloride cotransporters, e.g. Na-K-2Cl and K-Cl cotransporters, are activated to maintain fluid/ion homeostasis. Here we report the interaction of the stress-related serine-threonine kinases Ste20-related proline-alaninerich kinase (SPAK) and oxidative stress response 1 (OSR1) with the cotransporters KCC3, NKCC1, and NKCC2 but not KCC1 and KCC4. The interaction was identified using yeast two-hybrid assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
347
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(367 citation statements)
references
References 25 publications
20
347
0
Order By: Relevance
“…Four protein bands were detected in the WNK1 immunoprecipitate that were not seen in the control: two corresponded to WNK1 and WNK3, which was not a surprise since it is known that WNKs interact with each other [6]; a third band was the SDB84 antigen, but direct interaction between WNK1 and SDB84 was not confirmed; and the fourth band was a member of the STE20 family of kinases known as SPAK (STE20/SPS1-related proline/alanine-rich kinases). This last observation was pursued since it has been shown that SPAK, and the related OSR1 (oxidative stress response kinase-1), are involved in regulation of the basolateral isoform of NKCCl, and that WNK4 and SPAK can interact in a yeast two-hybrid system [9,10]. Of the four members of the STE20 family, the authors observed that WNK1 and WNK4 are able to physically interact with SPAK and OSR1, but not with the pseudokinases STRADα (STE20 related-adaptor α) and STRADβ.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Four protein bands were detected in the WNK1 immunoprecipitate that were not seen in the control: two corresponded to WNK1 and WNK3, which was not a surprise since it is known that WNKs interact with each other [6]; a third band was the SDB84 antigen, but direct interaction between WNK1 and SDB84 was not confirmed; and the fourth band was a member of the STE20 family of kinases known as SPAK (STE20/SPS1-related proline/alanine-rich kinases). This last observation was pursued since it has been shown that SPAK, and the related OSR1 (oxidative stress response kinase-1), are involved in regulation of the basolateral isoform of NKCCl, and that WNK4 and SPAK can interact in a yeast two-hybrid system [9,10]. Of the four members of the STE20 family, the authors observed that WNK1 and WNK4 are able to physically interact with SPAK and OSR1, but not with the pseudokinases STRADα (STE20 related-adaptor α) and STRADβ.…”
mentioning
confidence: 99%
“…The study of Vitari et al [8] is purely biochemical; however, a concomitant study provides the physiological counterpart of their findings. Gagnon et al [14], following their previous observations that SPAK interacts with NKCCl and that SPAK and WNK4 can interact in a yeast two-hybrid system [9,10], studied the effects of SPAK and WNK4 together on the activity of NKCCl. Gagnon et al [14] observed that co-injection of Xenopus laevis oocytes with NKCCl, SPAK and WNK4 cRNA resulted in a significant increase in NKCCl activity and insensitivity to external osmolarity or cell volume.…”
mentioning
confidence: 99%
“…The transmembrane region is responsible for ion binding and translocation (2), whereas the N-terminal cytosolic domain contains the regulatory phosphoacceptors (3) as well as a binding site for the regulatory kinase (4,5) and, in NKCC1, a binding site for the regulatory phosphatase (6). Three TMs have been shown to be involved in ion translocation, as determined with a chimera and single residue mutation approach (7,8); one of these is TM2, which is encoded by the NKCC2 splice region.…”
mentioning
confidence: 99%
“…For example, in glial cells missing, axons in the peripheral nerves are disorganized structurally, with regions of degeneration and swelling of the extracellular space (Banerjee et al, 2006). In fray mutants, ensheathment is abnormal in larval peripheral nerves and axons often are swollen in regions along the nerve (Leiserson et al, 2000), but recent studies in the mammalian homologue of fray have revealed that the mutation affects transporter activity that may be important in maintaining normal ionic homoeostasis, a function separate from the ensheathing function (Piechotta et al, 2002).…”
Section: Reported That Manducamentioning
confidence: 99%